Cavitation nanobubbles enhancing the flotation of microfine ilmenite and associated fundamentals - Fanfan Zhang; Wanchen Dong; Huijie Cai; Huaiyao Zhang; Xiangbo Fan; Yamin Kang; Yijun Cao; Guixia Fan (Ultrasonics Sonochemistry)
Nanobubbles (NBs) have been extensively utilized in mineral flotation, acting as secondary collectors to improve flotation efficiency. However, the fundamental interaction mechanisms between NBs and flotation collector remain unclear. In this study, NBs generated through hydrodynamic cavitation were introduced into the flotation of microfine ilmenite. With octyl hydroxamic acid (OHA) as the flotation collector, the effects of NBs on the flotation of microfine ilmenite were systematically investigated using a series of techniques. The results show that NBs not only improve the flotation recovery and flotation rate of microfine ilmenite, but also significantly lower OHA consumption while maintaining comparable recovery to the flotation without NBs. The measurements of the apparent size of ilmenite particles, contact angle, and the three-phase contact line between carrier bubbles and ilmenite surface indicate that NBs enhance the interaction between carrier bubbles and ilmenite particles during the flotation process. Furthermore, atomic force microscope imaging in different solutions confirms the adsorption of OHA-loaded NBs on the ilmenite surface. Most importantly, quartz crystal microbalance with dissipation monitoring results reveal that the presence of NBs leads to a reduction in OHA adsorption mass but an increase in adsorption rate at the ilmenite interface.